KEPEMIMPINAN PENDIDIKAN ISLAM DALAM PENGUATAN KARAKTER DISIPLIN BERIBADAH DI ERA DIGITALISASI - Siswadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to explain the role of Islamic educational leadership in strengthening students’ disciplined approach to worship amid the challenges and opportunities of the digital age, characterized by the widespread use of mobile devices and social media. The approach used is qualitative, employing a literature review method to analyze various sources on Islamic religious education, character education, digital literacy, and Islamic educational leadership. The findings indicate that visionary Islamic educational leadership grounded in Qur’anic–Prophetic values plays a strategic role through the formulation of vision and policies, the cultivation of a spiritual atmosphere, exemplary conduct, the fostering of communal worship, and the oversight of the wise use of technology. The strengthening of the character of worship discipline is carried out through the stages of transformation, transaction, and internalization of values, so that worship does not merely become a formal routine but is ingrained as a habit and part of the students’ personality. This study emphasizes the need for a model of Islamic educational leadership that is adaptive to technology while simultaneously capable of maintaining and reinforcing the younger generation’s commitment to worship in the digital age. Keywords: Islamic Educational Leadership, Discipline in Worship, Digital Era